ANALISIS DAYA DUKUNG BERDASARKAN PENYELIDIKAN TANAH LOKASI RENCANA RESERVOIR SPAM REGIONAL GORONTALO - Abdulkarim, Beryl; Fuad, Moh. Januar; Madjowa, Nona Fitriana (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
Construction Soil bearing capacity analysis is an important part of the reservoir construction process for the Gorontalo Regional Water Supply System (SPAM). The location of the soil investigation is located in Tunggulo Village, which is located in Kabila Bone District, Bone Bolango Regency. The characteristics and bearing capacity of the soil are the subjects of this study. In this study, both field and laboratory soil analysis were used. The characteristics of the soil at the planned reservoir construction site are silty sand with gravel and fine silty sand with varying consistencies, including very loose, springy, and medium density, according to soil investigation data. Field soil investigations show that the most common type of soil is sand, with an SPT value of medium density soil type consistency. The soil consistency against the CPT test qc value is a springy soil type, and the comparison of the bearing capacity and maximum load values ​​between CPT and SPT is greatly influenced by variations in soil type consistency